Communities of Practice and Recursive Publics - Zarate Vasquez, Sebastián (2024)
This article examines the development of digital fabrication in Peru, focusing on Lima Makers, the country’s first maker space. Through this case, the study explores the dynamics of socialization, collaborative identity, and innovation practices in a context where digital fabrication intersects with local artistic and technological culture. Utilizing the concepts of recursive publics, communities of practice, and infrastructuring, the analysis shows how Lima Makers fosters cohesion among its members and encourages creativity, while also facing challenges in forming active recursive publics involved in the governance of digital fabrication in Peru. Furthermore, the article argues that this local dynamic reflects a process of cultural appropriation and the creation of new technological identities in the global south.